Educational Impacts of Good Morals In the Light of the Holy Qur’an and the Prophetic Sunnah - Al-Hayti, Prof. Dr. Mohammed Nabhan Ibrahim Raheem Jaddi Al-Hayti Jaddi; Rahim, Prof. Dr.Abdullah Ibrahim Rahim; Al-Hayti, Assoc. Prof. Dr. Mahmoud Ibrahim Raheem Al-Hayti Raheem (Sulaimani Journal for Humanities, 2026)
Praise be to Allah, and peace and blessings be upon our master Muhammad, the Messenger of Allah, and upon his family, companions, and those who follow his guidance. One of the fundamental pillars of our Islamic faith—after belief in Allah and His Messenger—is the embodiment of noble character and high moral standards. These virtues refine the soul and polish the intellect, enabling a person to rise to a distinguished status among their peers and within society in this worldly life, and to attain the pleasure of Allah Almighty and the companionship of the beloved Prophet (peace be upon him) in the Hereafter. The stability and sustainability of both individual and societal life depend on adherence to good morals. Without them, a person cannot feel secure about themselves or their family, which in turn makes it difficult to fulfill their duties toward their nation and community. A brief look at the texts of the Holy Qur’an and the Prophetic Sunnah that emphasize ethical conduct reveals the high regard Islam places on morality. Ethics occupy a prominent status within Islamic rulings and legislation and are considered a key objective in preserving the unity and solidarity of the Muslim Ummah. This research seeks to highlight the most significant educational effects derived from good moral character when embraced by members of society—regardless of their position or status. It begins by defining "morals" linguistically and terminologically, including scholarly perspectives. It then clarifies the status of ethics in Islam, along with their foundations, sources, and distinguishing features. The study proceeds to identify and analyze the key educational effects drawn from selected Qur’anic verses and Prophetic traditions
Keywords: Educational effects; good morals; the Holy Quran; the Sunnah; society